Effects of Advanced Practice Providers on Single-specialty Surgical Practice. Issue 1 (3rd January 2023) - Hollenbeck, Brent K.; Kaufman, Samuel R.; Oerline, Mary; Modi, Parth K.; Caram, Megan E. V.; Shahinian, Vahakn B.; Ellimoottil, Chad
Abstract : Objective: To assess the effects of adding advanced practice providers to surgical practices on surgical complications, readmissions, mortality, episode spending, length of stay, and access to care. Summary Background Data: There has been substantial growth in the number of nurse practitioners and physician assistants (ie, advanced practice providers) in the United States. The extent to which advanced practice providers have been integrated into surgical practice, and their impact on surgical outcomes and access is unclear. Methods: Using a 20% sample of national Medicare claims, we performed a retrospective cohort study of fee-for-service beneficiaries undergoing one of 4 major procedures (coronary artery bypass graft, colectomy, major joint replacement, and cystectomy) between 2010 and 2016. We limited our study population for each procedure to patients treated by single-specialty surgical groups to ensure that the advanced practice providers have direct interactions with its surgeons and patients. All outcomes were measured at the practice level for the year before and the year after the addition of the first advanced practice provider. Outcomes included: complications, readmission, mortality, episode payments, length of stay. Models were adjusted for age, race, sex, comorbidity, socioeconomic class and procedure type. Secondary outcome: practice-level office visits by surgical group type. Results: The number of advanced practice providers increased by 13%, from 6713 to 7596 between 2010 and 2016. The largest relative increases occurred in general (46.9%) and urologic (27.6%) surgical practices. The year after an advanced practice provider was added to a surgical practice, the odds of complications were 17% and 16% lower at 30- and 90-days postprocedure, respectively. Additionally, 90-day readmissions were 18% less likely and length of stay was 0.33 days shorter (a 7.1% reduction). Average 30-day and 90-day episode spending was 1294.73 and 1427.76 lower, respectively ( P < 0.001). General surgical, orthopedic, and urology practices realized increases of 49.0 (95% CI 13.5–84.5), 112.0 (95% CI 83.0–140.5), and 205.0 (95% CI 117.5–292.0) in-office visits per surgeon, respectively. Conclusions: The addition of advanced practice providers to single-specialty surgical groups is associated with improvements in surgical outcomes and access. Future work should clarify the mechanisms by which advanced practice providers within surgical practices contribute to health outcomes to identify best practices for deployment.